2019
DOI: 10.1200/jco.2019.37.15_suppl.e20542
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mutations in the EGFR gene in patients diagnosed with lung cancer.

Abstract: e20542 Background: Lung cancer is the most common malignant tumor after breast cancer and is the main cause of cancer mortality. Mutations in the EGFR gene typical of lung cancer lead to constitutive activation of the epidermal growth factor receptor and malignant cell transformation. The purpose of this study was to identify associations between double and triple mutations in EGFR and clinical and pathological characteristics of patients in the South of Russia diagnosed with lung cancer. Methods: DNA was ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the previous studies, the double mutations consisted of exon 20 T790M, which has been identified as primary factors in 1 st and 2 nd EGFR TKI-resistance. 38 Barnet et al also showed shorter PFS in a patient with co-mutations of exon 19 with noncommon EGFR mutations including exon 20, T90M, and PIK3CA. 39 This differs from the current study, which looked at exon 19 and exon 21 mutations.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In the previous studies, the double mutations consisted of exon 20 T790M, which has been identified as primary factors in 1 st and 2 nd EGFR TKI-resistance. 38 Barnet et al also showed shorter PFS in a patient with co-mutations of exon 19 with noncommon EGFR mutations including exon 20, T90M, and PIK3CA. 39 This differs from the current study, which looked at exon 19 and exon 21 mutations.…”
Section: Resultsmentioning
confidence: 90%
“…The various studies tried to identify the impact of double mutations or triple mutations of EGFR in clinicopathology characteristics in lung cancer patients. 37,38 All previous studies showed poorer outcomes with multiple mutations compared with single EGFR mutations. 37,38 Nevertheless, in this study, double mutations of exon 19 and exon 21 showed a better outcome in both OS and PFS compared with single mutations of exon 19.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When two or three mutations in one tumor is seen with combination of for example ex19del-ex20ins with the T790M, the frequency is at 1.7% Overall, the frequency of having two-three gene mutations in EGFR is 0.33% so it is especially rare. 7 There are other mutations rarer in the exon 18-25 that tend to reflect poor prognosis. 8 About 10% of nonsmall cell lung cancers respond well with tyrosine kinase inhibitors (TKIs) that target EGFR.…”
mentioning
confidence: 99%